Blessed Are Those Who Do Not Know the Future of the Church. A Plea for Negative Ecclesiology - Jos, Moons (Studia Theologica Varsaviensia, 2022)
What will the future of the church look like? What type of mission should the church commit herself to? Rather than elaborating one more answer to these important questions, I have pleaded for negative ecclesiology and ‘the grace of self-doubt’. This is not to replace the answers that are given, but to safeguard sufficient openness in these answers. By abstaining from certitude, the church may more easily hear what the Spirit is saying to the churches beyond our own, human and therefore narrow minded understandings. My brief discussions on the Trinity, Ignatian spiritual direction and synodality were meant to illustrate that ‘wise ignorance’ and openness to surprises are present in some other dimensions of the Christian faith and theology and may, therefore, be safely adopted in reflections on the future of the church. A great fruit of negative ecclesiology is that it allows for change, that is, for a new understanding of God and therefore a new understanding of the church. Because the Apostles allowed for uncertainty, they could accept that God’s grace did not require circumcision and Jewish purity regulations – a crucial revolution in the early Christian church. Similarly, during the Second Vatican Council the bishops did not insist on using the same words, and were therefore able to embrace another, more pastoral style of magisterial teaching. In the same way, negative ecclesiology can help the church – its leadership as much as lay faithful – to be open to new perspectives on church and on mission. It may help to confront the painful truth that in the West the omnipresence of the church belongs to a past era and that in the church’s role in society is becoming a marginal one. It may help the faithful and church leadership to embrace the task of bringing the number of church buildings more in line with the church’s current position in society – that is, to abolish a significant number of churches. Finally, it may help to reconceive the church’s prophetic voice into a more dialogical and humble voice, which testifies rather than criticizes, and that is willing to learn as much as to teach.